2023
DOI: 10.1007/s10903-023-01464-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Admission Among Migrants Before and During Pandemic: a Retrospective Study in Acute Psychiatric Ward in Bologna, Italy

Abstract: Previous evidence showed significant discrepancies in psychiatric services utilization between migrants and reference populations. Our study aims were to evaluate incidence and characteristics of psychiatric hospitalizations of migrant patients compared with reference populations and to assess how the COVID-19 pandemic affected admissions. All patients admitted to the psychiatric ward "SPDC-Malpighi" of the Bologna Mental Health Department from 01/01/2018 to 31/12/2020 were included. Differences in sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Another study showed that the risk of admission to a psychiatric unit is three times higher in migrants compared to non-migrants; compulsory admission among young migrants (15 to 24 years old) is four times higher. According to the same study, 20.7% of sub-Saharan Africans were admitted to psychiatric units versus 6.2% in the general population, and 17.9% of North Africans versus 8.7% in the general population (22). 2.…”
Section: Epidemiological Contextmentioning
confidence: 94%
“…Another study showed that the risk of admission to a psychiatric unit is three times higher in migrants compared to non-migrants; compulsory admission among young migrants (15 to 24 years old) is four times higher. According to the same study, 20.7% of sub-Saharan Africans were admitted to psychiatric units versus 6.2% in the general population, and 17.9% of North Africans versus 8.7% in the general population (22). 2.…”
Section: Epidemiological Contextmentioning
confidence: 94%
“…Así mismo, se consideran los niveles de gravedad de los síntomas del paciente y el historial psicosocial, siendo esta importante para detectar causas como maltratos, abusos, estrés, entre otros. La revisión realizada evidenció en algunos casos el uso de autoinformes y de registros médicos electrónicos (EHR), para los cuales usaron un formulario electrónico personalizado de informe de casos (REDCap)(22).Las características sociodemográficas de los pacientes es una información a tener en cuenta, esta se realiza con las categorías de la edad del paciente, número de visitas al departamento de emergencias, situación familiar, diagnóstico psiquiátrico; de allí que se les llame de tipo sociodemográfico(32). De la misma manera, el registro puede abarcar datos generales del paciente como puede ser el sexo, la fecha de nacimiento, fecha de ingreso al departamento de emergencias.Por otro lado, existen en esta categoría los cuestionarios, en los cuales se señalan los síntomas psiquiátricos que el ingresante puede poseer tales como el trastorno alimenticio, agitación, intento de suicidio y antecedentes del mismo(36,35).…”
unclassified